Who Needs a Methodological Course about Death in the Poetry for Children and Youth? Students' Motivation for This Course, Their Concepts and Experience Related to Death - Vladimir M. Vukomanović Rastegorac (University of Belgrade, Teacher Education Faculty, 2023)
Psychological studies have shown that children begin to think about death at an early age and have encouraged a rethinking of the concept of possible education about death. For this reason, the course entitled "Methodological Approach to the Theme of Death in Poetry for Children and Youth" was launched at the Teacher Education Faculty in Belgrade. A short description of the course is given in the first part of this paper. Тhe paper then elaborates on the research conducted within the course, the goal of which was to describe: 1) students' motivation for this course and 2) students' expectations regarding the course content. In addition, given that the target audience is important for the manner in which the content will be presented, we also examined the course participants': 3) conceptualization of death; 4) their experience related to death; 5) opinions regarding discussions about death with children; 6) knowledge of literary texts that deal with death. The method of verbal and visual associations and a questionnaire were used for data collection. Data analysis has shown that: 1) the course title is what motivates students the most to choose this course; 2) students are interested in children's attitudes about death, the way death is thematized in children's literature, as well as understanding the phenomenon of death in general; 3) the elements of metaphysical concept of death are prevalent among students; 4) the largest number of students has experienced the death of a family member, a friend, or a pet; 5) students think that children's age, experience related to death, interests, and cognitive maturity have to be taken into consideration when talking with children about death; 6) students are more familiar with the prose texts than poetry for children thematizing death.